Improvement of photocatalytic activity of silicate paints by removal of K2SO4. (August 2015) - Tryba, B.; Wrobel, R.J.; Homa, P.; Morawski, A.W.
Abstract: Some organic and mineral photocatalytic paints produced by Pigment company (Poland) were tested for the decomposition of benzo[a]pyrene (BaP) under UV–Vis. It appeared that latex (LX) and acrylic (IN) paints were more photoactive than mineral (FA and DR) ones. It was concluded that large amount of calcium carbonate and the presence of potassium sulfate in the mineral paints were detrimental for their photocatalytic activity. Potassium sulfate present in the paint formula resulted in the limiting access to the active anatase phase of TiO2 . However potassium sulfate is soluble in water, therefore it was removed from the paint surface by simply washing with distilled water and then enhanced activity of the photocatalytic mineral paints was observed. Graphical abstract: Highlights: K2 SO4 present in the photocatalytic silicate paints inhibits their activity. Removal of K2 SO4 by rinsing with H2 O improves photocatalytic activity of paints. CaCO3 in paints increases porosity and roughness of surface. High roughness of paint surface limits access of light to the photoactive TiO2 . Porous structure of CaCO3 promotes adsorption of pollutant without decomposition.